1984
DOI: 10.1021/ja00337a022
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation patterns for iron(II) porphyrins. Peroxo and ferryl (FeIVO) intermediates detected by proton nuclear magnetic resonance spectroscopy during the oxygenation of (tetramesitylporphyrin)iron(II)

Abstract: 7779such as 2 are expected to be the most sensitive of aromatics to ring current effects, for normal biphenyl-type aromatics interaction between the rings will be more readily observed through UV spectra than nuclear magnetic resonance data. Experimental Section'H NMR spectra were determined in CDCI, on a Perkin-Elmer R32 (90 MHz) spectrometer and are reported in parts per million downfield from tetramethylsilane as internal standard. UV spectra were determined in cyclohexane on a Cary 17 spectrophotometer. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
110
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 9 publications
18
110
0
Order By: Relevance
“…This is most certainly due to the increased stability ofhigh-valent metals when bound to highly basic oxo ligands. The reactivity of the iron(IV)-oxo species generated electrochemically is very similar to that reported for the iron(IV)-oxo species produced chemically (25)(26)(27)(28). The decomposition of the iron(IV)-oxo porphyrin at temperatures above -50'C shows that it is more chemically reactive than the iron(III) porphyrin ir-cation radical, even though the redox potential of the latter is more positive.…”
Section: Discussionsupporting
confidence: 75%
“…This is most certainly due to the increased stability ofhigh-valent metals when bound to highly basic oxo ligands. The reactivity of the iron(IV)-oxo species generated electrochemically is very similar to that reported for the iron(IV)-oxo species produced chemically (25)(26)(27)(28). The decomposition of the iron(IV)-oxo porphyrin at temperatures above -50'C shows that it is more chemically reactive than the iron(III) porphyrin ir-cation radical, even though the redox potential of the latter is more positive.…”
Section: Discussionsupporting
confidence: 75%
“…It should be noted that the pyrrole-H chemical shift (-63 ppm at -60°C, Table 1) 66 of this complex is much more negative than that for the bis(methoxide) complex discussed in the previous paragraph, suggesting a different electron configuration for the phenyl complex, i.e., ( 69 A similar pattern is observed for the N-methylimidazole adduct of this species (Table 1). 69 This pattern of small upfield shifts for both types of protons is unlike that predicted for any distribution of metal d electrons, and it likely results from most of the spin density being delocalized to the oxo group, rather than the porphyrin ring. In fact, theoretical calculations of some 20 years ago indicated that the small upfield nature of both pyrrole-H and meso-H isotropic shifts is consistent with most of the spin density being on the oxo group.…”
Section: H Nmr Spectroscopy Of Paramagnetic Iron Macrocycle Complexesmentioning
confidence: 84%
“…71,72 Hence, in terms of observed chemical shifts, the 1 H NMR spectra of oxoiron-(IV) porphyrinates behave more like diamagnetic d 6 Fe(II) bound to a six-electron (two unpaired) oxygen atom, rather than paramagnetic d 4 Fe(IV) centers. [67][68][69][70][71][72] …”
Section: H Nmr Spectroscopy Of Paramagnetic Iron Macrocycle Complexesmentioning
confidence: 99%
“…Second, coordination of oxygen to the five coordinate species at room temperature leads rapidly and irreversibly to the formation of bridged 0x0-iron(II1) species (2,3). Autoxidation of the iron centre proceeds via the initial formation of a monomeric iron-dioxygen adduct, followed by the reaction with a second iron(I1) porphyrin unit (4).…”
Section: Introductionmentioning
confidence: 99%